(untitled) (Journal of Asian Development Studies, 2023)
During the era or administration of General Pervez Musharraf, political parties played various roles in Pakistan’s democratic process from 1999 to 2008. It examines how these parties are suppressed, appropriated, and resilient in an authoritarian environment, revealing the complex interactions between the political parties and the military government. After the takeover of General Pervez Musharraf in 1999, democratic institutions were suspended, and political freedoms were significantly curtailed. Mainly, personalities associated with former civilian regimes were marginalized and subjected to restrictions. Under Musharraf’s leadership, the Political Parties Order 2002 was enacted, severely limiting party activities. Despite these challenges, political parties remained a significant component of Pakistan’s political environment. While some were coopted or formed connections with the military government, others were apprehended to fight and organize against the authoritarian dictatorship. General elections in 2002 were held in a confined space, which sparked allegations of rigging. The Pakistan People’s Party (PPP), led by Benazir Bhutto, was notable among the opposition and was involved in overthrowing Musharraf’s government. Opposition groups and civil society organizations persisted in their protests and demanded the restoration of civilian authority. This article will highlight political parties’ resistance to authoritarianism and their critical role in Pakistan’s final switch to civilian rule in 2008. It sheds insight into the complex interactions between political figures and the military dictatorship during a turbulent time in Pakistan’s political history.